Efecto de dosis creciente de nitrógeno en la producción de pepino híbrido. - Muñoz Chuya, Angie Lissett (Machala : Universidad Técnica de Machala, 2023)
The study was conducted at the "The Mouth" Farm located in the Palmales-Arenillas, El Oro, Ecuador, with the aim of determining the effect of different nitrogen doses on the cucumber crop (Cucumis sativus, L) hybrid Humacro, focusing on the yield and profitability of the crop. The experimental design was a Completely Randomized Block Design (CRBD), with replicated plots to minimize variability, employing 5 treatments with recommended doses (T1: 25% RD; T2: 50% RD; T3: 75% RD; T4: 100% RD; T5: 125% RD) and 1 control treatment (T6: 0% RD). Field materials and tools were used for planting, maintenance, and harvesting of the crop, as well as laboratory instruments for measuring the established parameters. The variables to be evaluated included weight (g), diameter (mm), length (cm), quality, and production (t/ha) of the fruit. Among the results, treatment T5 showed the best outcomes in the fruit weight variable (489.82 grams), while treatments T4 and T5 exhibited lengths and diameters reaching 23.47 cm and 23.05 cm, and 59.22 mm and 58.96 mm, respectively. Regarding fruit quality, all treatments were statistically homogeneous, again highlighting the mentioned treatments; in terms of productivity, no treatment exceeded the established level for estimating nutritional requirements (100 t/ha), but there were values that approached this figure, particularly emphasizing treatments T4 and T5. In conclusion, the information provided in this study on the influence of increasing nitrogen doses can contribute to improving agricultural practices and productivity in cucumber cultivation.
El estudio se realizó en la Finca "La Bocana" ubicada en la parroquia Palmales-Arenillas, El Oro, Ecuador, con el objetivo de determinar el efecto de diferentes dosis de nitrógeno en el cultivo de pepino (Cucumis sativus, L) híbrido Humacro, sobre en el rendimiento y rentabilidad del cultivo. El diseño experimental fue Bloques Completamente Aleatorio (DBCA), con parcelas replicadas para minimizar la variabilidad, empleándose 5 tratamientos con dosis recomendada -DR- (T1: 25%DR; T2: 50%DR; T3: 75%DR; T4: 100%DR; T5: 125%DR) y 1 tratamiento testigo (T6: 0%DR). Se emplearon materiales de campo y herramientas para la siembra, mantenimiento y cosecha del cultivo, como también instrumentos de laboratorio para la medición de los parámetros establecidos. Las variables a evaluar fueron peso (g), diámetro (mm), longitud (cm), calidad y producción (t/ha) del fruto. Entre los resultados, se destaca que el tratamiento T5 mostró los mejores resultados en la variable peso del fruto (489,82 gramos), mientras que en el diámetro y longitud del fruto los tratamientos T4 y T5 mostraron longitudes y diámetros que alcanzan los 23,47cm y 23,05cm, y, 59,22 mm y 58,96mm respectivamente, en lo que respecta a la calidad de fruto, todos los tratamientos son estadísticamente homogéneos, resaltando nuevamente los tratamientos mencionados; y en cuanto a la productividad, ningún tratamiento superó el nivel establecido para la estimación de los requerimientos nutricionales (100 t/ha), pero existieron valores que bordearon este valor, destacando nuevamente los tratamientos T4 y T5. En conclusión, la información proporcionada en este estudio sobre la influencia de las dosis crecientes de nitrógeno, puede contribuir a mejorar las prácticas agrícolas y la productividad en el cultivo de pepino.
Keywords: PEPINO; RENDIMIENTO; DOSIFICACION; PRODUCCION